Outline of a Linguistic Model for the Study of Emerging Naming - Jackiewicz, Agata (Kalbotyra, 2021)
The article presents the outline of a linguistic model that is part of a methodology for identifying and analyzing emerging or referentially unstable namings, such as cultural appropriation, street harassment, climate refugee or ecocide. The model and the method are intended to guide the interpretation – manual or semi-automatic – of the referential expressions, according to the semantic-cognitive type of the designated entity (human entity, social process, event, etc.), but also taking into account interdiscursive negotiations that affect the choice of terms and their uses. The proposed approach is original and is based on several guiding ideas: (1) take into account the complexity of the naming and the entanglement of his different facets which are categorization, meaning, performativity and valuation (desirability, preferences, social norms), (2) target the development phase of the naming (observe how speakers deal with the unstable): for this purpose, we will use the notion of identification between weak or identified entities and strong or reference entities, (3) report in an integrated way the referential elaboration of knowledge, the lexical and semantic elaboration of expressions, and the expression of intersubjective attitudes. The scientific framework combines three main disciplinary areas: automatic language processing (construction and representation of knowledge, reference), semantics (elaboration of meanings) and discourse analysis (interdiscursive elaboration of concepts and terms).